Emerging regional human rights systems in Asia / Tae-Ung Baik, Associate Professor, William S. Richardson School of Law, University of Hawaiʻi at Manoa. - Baik, Tae-Ung (Cambridge University Press, 2012)
Asia is the only area in the world that does not have a human rights court or commission covering the region as a whole. However, a close look at recent developments in the region, especially in East Asia, shows that a human rights system is emerging. Various activities and initiatives for human rights cooperation are developing in Asia at the regional, sub-regional and national levels. Since the establishment of the ASEAN human rights body (AICHR) in 2009, the need for a review of the regional human rights mechanisms in Asia is stronger than ever. With a primary focus on twenty-three East Asian states, Tae-Ung Baik highlights the significant changes that have taken place in recent decades and demonstrates that the constituent elements of a human rights system (norms, institutions and modes of implementation) are developing in Asia.